(untitled) (Palimpsesto, 2020)
This paper puts attention on the collected letters that Angel Guido (Rosario, 1896-1960) and Ricardo Rojas (San Miguel de Tucumán 1882 - Buenos Aires 1957) exchanged between 1931 and 1933 as regards the prestigious Guggenheim Fellowship granted to the rosarino architect and the consequent travel to the United States, a meridian fact in his intellectual itinerary. So, we intend to interrogate a writing practice along with his ideological interventions through the autobiographical continent (Antières y Dabbadie, 2019) or laboratory of ideas (Maíz, 2018) that conforms this selection of papers belonging to a major collection of unpublished letters (1925-1955). To say on other terms, we intend to map the interaction of individual matters (which was the architect´s purpose after the Fellowship? which were the changes in his intellectual horizon? which thoughts were put into movement in his professional project during the American travel?) within a wider context where the leading question was the search for an American architecture, emancipated and with “Eurindica” source.